MCITP self-paced training kit (Exam 70-685) : Windows 7 enterprise desktop support technician - Northrup, Tony (Microsoft Press WashingtonUS, 2010)
Focuses on identifying cause of and resolution of desktop application, networking and security ssues; managing and maintaining systems that run Windows 7 client, and supporting mobile users.